The Church in the system of formation of power institutions of the voluntary movement in the South of Russia: peculiarities of establishing the Black sea diocese in 1918?1919 - Nikita Kiyashko (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2019)
This article analyses the reasons for the administrative and territorial transformations of the southern dioceses after the February revolution of 1917 in the context of the internal policy of the government in the Southern Russia. With the active support of A. I. Denikin, who was interested in strengthening church life, the reform had a signifi cant infl uence on the change of the position of the church and led to establishing independent dioceses which were united under the Temporary Supreme Church Administration of Southern Russia. The city of Novorossiysk came to be prominent as one of the centres of the Voluntary Movement, while relations with the socialist government of Abkhasia deteriorated. With this background, the region acquired independence of the church, and a separate Black Sea diocese was established, which corresponded well not only with Denikin’s policy, but also with the actual needs of the population of the region. The formation of a new administrative and church landscape not only intensifi ed church activities, but also provided grounds for the future southern dioceses.